2019
DOI: 10.1371/journal.pone.0225215
|View full text |Cite
|
Sign up to set email alerts
|

Fiber stiffness, pore size and adhesion control migratory phenotype of MDA-MB-231 cells in collagen gels

Abstract: Cancer cell migration is influenced by cellular phenotype and behavior as well as by the mechanical and chemical properties of the environment. Furthermore, many cancer cells show plasticity of their phenotype and adapt it to the properties of the environment. Here, we study the influence of fiber stiffness, confinement, and adhesion properties on cancer cell migration in porous collagen gels. Collagen gels with soft fibers abrogate migration and promote a round, non-invasive phenotype. Stiffer collagen fibers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 41 publications
3
31
0
Order By: Relevance
“…Furthermore, the probability of observing large angles between two steps increases with increasing time lag. This is indicative of the tendency of the migrating 10 20 30 0 counts τ (minutes) p A 25% 10 1 10 2 10 3 10 4 10 5 0 50% 10 1 10 2 10 3 10 4 10 5 0 67% 10 1 10 2 10 3 10 4 10 5 0 75% 10 1 10 2 10 3 10 4 10 5 0 25% 50% cells to do 180°turns and backtrack; a behavior that is more pronounced in the higher ECM concentrations (67% and 75%), which is in accordance with other observations Wu et al 2014, Geiger et al 2019, Wu et al 2015. A possible explanation for this is that cells -due to high adhesion and small ECM pore sizes -turn around and follow the beaten micro-tracks in the ECM back towards the spheroid.…”
Section: Cells Migrate Both With Directionality and Persistencesupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the probability of observing large angles between two steps increases with increasing time lag. This is indicative of the tendency of the migrating 10 20 30 0 counts τ (minutes) p A 25% 10 1 10 2 10 3 10 4 10 5 0 50% 10 1 10 2 10 3 10 4 10 5 0 67% 10 1 10 2 10 3 10 4 10 5 0 75% 10 1 10 2 10 3 10 4 10 5 0 25% 50% cells to do 180°turns and backtrack; a behavior that is more pronounced in the higher ECM concentrations (67% and 75%), which is in accordance with other observations Wu et al 2014, Geiger et al 2019, Wu et al 2015. A possible explanation for this is that cells -due to high adhesion and small ECM pore sizes -turn around and follow the beaten micro-tracks in the ECM back towards the spheroid.…”
Section: Cells Migrate Both With Directionality and Persistencesupporting
confidence: 90%
“…However, Matrigel™ has been found to play a dual role: While the presence of Matrigel™ in collagen gels promoted migration of lung cancer cells (H1299) at low concentration, it hindered migration at higher concentrations, probably due to increased adhesion-ligand concentration Anguiano et al 2017. Thus, our hypothesis -that increased ECM concentration favors increased single cell migration -might be counteracted by increased adhesion-ligand concentration and result in no apparent ECM concentration dependence Geiger et al 2019. Moreover, earlier studies suggest that proteolysis serves as an important additional mechanism for migration of cancer cells, allowing them to move through the matrix -no matter how dense it is Zaman et al 2006, Valastyan and Weinberg 2011, Koh et al 2018.…”
Section: Discussionmentioning
confidence: 76%
“…It is of interest to investigate whether and how cells adapt their stiffness during tumour detachment and invasion as the disease progresses. It has been shown that reduced cell-cell adhesion decreases cell stiffness (Omidvar et al 2014) and increases migration (Geiger et al 2019) and that increased migration and decreased cell stiffness are directly correlated (Guck et al 2005, Remmerbach et al 2009). However, it is not yet known whether these observations of cellular mechanics translate directly to physiologically relevant environments that mimic the tumour-cell detachment process.…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, RhoA-dependent signaling drastically reduces Rac1 activity, suppressing the formation of pseudopods, and triggering the shift to an amoeboid-like phenotype [ 154 ]. Similarly, pharmacological inhibition of integrins and MMPs in mesenchymal tumor cells promotes MAT in hydrogels with pores smaller than the cell size, regardless of their composition [ 74 , 155 , 156 ]. This amoeboid-mesenchymal plasticity exhibited by tumor cells allows more efficient invasion compared to non-adaptive cells, especially in high-confined-hypoxic environments [ 154 ].…”
Section: Ecm Mechanobiological Stimuli Govern Cell Migration Plastmentioning
confidence: 99%